Investigating the quality of online discussion forums for Life Sciences courses - Mohlala, Shamah (My University, 2022)
Most online discussions are barely covered within a given time frame, than they would have been, if the content was taught in a face to face setting. Due to time constrains, if students skipped a session or perhaps the lecturer had to skim over the content; students had to do their own research at their own time in order not to fall behind with the content taught. Moreover, one of the lecturers’ strategic roles was to ensure that students participate meaningfully in online discussion forums during the teaching and learning process. This study pursued to establish how the quality of online discussion forums is vested between the lecturers and the students, in other words, how lecturers conduct online discussion forums. Five lecturers took part in the interviews, and further data from the BigBlueButton app including recordings were used to analyse how students and lecturers interacted in online discussion forums. The findings of the study indicated the common and major challenge of the online discussion forums as being the issue of internet connectivity. Online discussion forums, on the other hand, benefit both students and lecturers who are exploring new digitalised ways of teaching and learning.
A research report presented in partial fulfilment of the requirement for the degree of Masters in Education by Coursework and Research Report to the Faculty of Humanities, School of Education, University of the Witwatersrand, 2022